A unimolecular channel formed by dual helical peptide modified pillar[5]arene: correlating transmembrane transport properties with antimicrobial activity and haemolytic toxicity. Issue 83 (9th October 2017) - Xin, Pengyang; Sun, Yonghui; Kong, Huiyuan; Wang, Yaodong; Tan, Si; Guo, Jingjing; Jiang, Tao; Dong, Wenpei; Chen, Chang-Po
Abstract : Five unimolecular channels with different lengths are presented. The varying length of these channels has significant impact on their transport properties. Abstract : Five unimolecular channels with different lengths are presented. The varying length of these channels has significant impact on their transmembrane transport properties, which are directly correlated with their antimicrobial activity and inversely correlated with their haemolytic toxicity. By further structural optimization, these new channels could reach high antimicrobial activity and very low haemolytic toxicity, with the potential to serve as systemic antibiotics.